Tailored Synthesis of Octopus‐type Janus Nanoparticles for Synergistic Actively‐Targeted and Chemo‐Photothermal Therapy. (6th January 2016) - Zhang, Lingyu; Chen, Yinyin; Li, Zilu; Li, Lu; Saint‐Cricq, Philippe; Li, Chunxia; Lin, Jun; Wang, Chungang; Su, Zhongmin; Zink, Jeffrey I.
Abstract: A facile, reproducible, and scalable method was explored to construct uniform Au@poly(acrylic acid) (PAA) Janus nanoparticles (JNPs). The as‐prepared JNPs were used as templates to preferentially grow a mesoporous silica (mSiO2 ) shell and Au branches separately modified with methoxy‐poly(ethylene glycol)‐thiol (PEG) to improve their stability, and lactobionic acid (LA) for tumor‐specific targeting. The obtained octopus‐type PEG‐Au‐PAA/mSiO2 ‐LA Janus NPs (PEG‐OJNP‐LA) possess pH and NIR dual‐responsive release properties. Moreover, DOX‐loaded PEG‐OJNP‐LA, upon 808 nm NIR light irradiation, exhibit obviously higher toxicity at the cellular and animal levels compared with chemotherapy or photothermal therapy alone, indicating the PEG‐OJNP‐LA could be utilized as a multifunctional nanoplatform for in vitro and in vivo actively‐targeted and chemo‐photothermal cancer therapy.